A game model of new and remanufactured goods, brown and green consumers, and market share dominance - Amit Batabyal; Hamid Beladi (European Regional Science Association (ERSA), 2016)
The n total consumers in the market for a particular good are made up of b brown and g green consumers so that b+g=n. The b brown (g green) consumers are not (are) environmentally conscious and hence they prefer to buy a new (remanufactured) good denoted by N and R respectively. By strategically purchasing or not purchasing the N and the R goods, the brown and the green consumers attempt to create a dominant market share for their preferred good. In this setting, we study three issues. First, we delineate the game between the brown and the green consumers in normal form and then solve for the Nash equilibrium when n=2 and b=1. Second, we find all the Nash equilibria of this game between brown and green consumers when n>2 is an even number and b=g=n/2. Finally, we increase the cost of purchasing the new and the remanufactured goods and then study how this increase affects the answers obtained for the above two issues.
Keywords: D11; Q20; 330; Brown Consumer; Green Consumer; Market Share; New Good; Remanufactured Good